Implementation of the findings of the African Commission on Human and Peoples' Rights - Murray, Rachel (Rachel H.); Long, Debra (Cambridge, United Kingdom : Cambridge University Press, 2015)
"An 'implementation crisis' has been identified in the enforcement of rulings of UN and regional human rights bodies and fundamental but crucial questions remain unanswered: what exactly does it mean to implement and comply with international and regional human rights decisions; and what factors influence whether a state implements and complies or not? Much more is now known about the work of the African Commission on Human and Peoples' Rights, but a gap still exists in the literature on the implementation of the findings of the Commission. This book draws upon the data and evaluation from a four-year research project, analysing the range of pronouncements of the African Commission, including its decisions on individual communications, provisional measures, resolutions, and promotional and protective mission reports. It investigates the extent to which States implement these findings and examines how that implementation is monitored by others"--
1. Introduction -- 2. Soft/hard, binding/non-binding: a useful distinction? -- 3. Concepts of implementation, compliance and follow-up -- 4. Range and status of findings from the African Commission on Human and Peoples' Rights -- 5. The 'use' of the African Commission findings at the national, regional and international levels -- 6. Follow-up and implementation at the national level -- 7. What role should the African Commission play in following up its own findings? -- 8. The relationship with the African Court on Human and Peoples' Rights -- 9. The role of the African Union -- 10. Conclusion -- Appendix 1. African Charter on Human and People's Rights -- Appendix 2. Protocol to the African Charter on the Establishment of the African Court on Human and Peoples' Rights -- Appendix C. Rules of procedure of the African Commission on Human and Peoples' Rights -- Appendix 4. Resolution on the importance of the implementation of the recommendations of the African Commission on Human and Peoples' Rights by states parties.
Includes bibliographical references (pages 266-291) and index.
Keywords: African Commission on Human and Peoples' Rights; African Commission on Human and Peoples' Rights; Human Rights Africa (Organization); Human rights -- Africa; Africans -- Legal status, laws, etc. -- Africa; Humanitarian law -- Africa; Africans -- Legal status, laws, etc; Humanitarian law; Africa